2011
DOI: 10.3382/ps.2011-01475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, vitamin D3, and fructooligosaccharides on bone growth and skeletal integrity of broiler chicks

Abstract: A study was conducted to evaluate the effects of age, vitamin D(3), and fructooligosaccharides (FOS) on bone mineral density (BMD), bone mineral content (BMC), cortical thickness, cortical and trabecular area, and mechanical properties in broiler chicks using peripheral quantitative computed tomography and mechanical testing. A total of 54 male broiler chicks (1 d old) were placed in battery brooders and fed a corn-soybean starter diet for 7 d. After 7 d, the chicks were randomly assigned to pens of 3 birds ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
2
16
0
2
Order By: Relevance
“…Consumption of combined short-and longchain inulin-type fructans increased Ca absorption and enhanced bone mineralization during pubertal growth of human (Abrams et al 2005). However, Swiatkiewicz et al (2011) and Kim et al (2011) reported that FOS or inulin do not improve the bone growth and skeletal integrity of broiler chicks. In the present study, we found the positive effects of FPCM on calcium retention in bone.…”
Section: Bone Mineralizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Consumption of combined short-and longchain inulin-type fructans increased Ca absorption and enhanced bone mineralization during pubertal growth of human (Abrams et al 2005). However, Swiatkiewicz et al (2011) and Kim et al (2011) reported that FOS or inulin do not improve the bone growth and skeletal integrity of broiler chicks. In the present study, we found the positive effects of FPCM on calcium retention in bone.…”
Section: Bone Mineralizationmentioning
confidence: 97%
“…However, another research showed that FOS or inulin do not improve the bone growth and skeletal integrity of broiler chicks (Kim et al 2011;Swiatkiewicz et al 2011). These data suggest that oligosaccharides may modulate animal mineral metabolism.…”
Section: Introductionmentioning
confidence: 97%
“…Vitamin D deficiency impaired bone mineralization, and resulted in low tibia breaking-strength, weight, length, width, ash weight values and low ash, Ca and P percentages in broilers in groups 1 to 6 in the present study. High levels of vitamin D 3 increased bone growth and mineral deposition in broiler chickens (Whitehead et al, 2004;Kim et al, 2011). As a metabolite of vitamin D, 1α-OH-D 3 has higher bioavailability than vitamin D 3 .…”
Section: Tibia Mineralizationmentioning
confidence: 99%
“…However, trabecular bone mineral density was not affected by dietary treatment. Likewise, Kim et al (32) and Jendral et al (33) found that total and cortical bone mineral density discriminated between the treatments with no effect on trabecular bone mineral density in, respectively, broiler chicks at day 21 and hens at 65 weeks of age. As stated by these authors, these results could be due to excessive bone resorption from the endosteal surface located at the inner edge of the cortical shell.…”
Section: Necessity Of a Repletionmentioning
confidence: 94%